REMOVAL OF SIDE ILLUMINATION IN THE IMAGE PLANE IN TWO-MIRROR PANCRATYC SYSTEM FOR COLLIMATOR: REMOVAL OF SIDE ILLUMINATION IN THE IMAGE PLANE IN TWO-MIRROR PANCRATYC SYSTEM FOR COLLIMATOR - Zhekov , Zhivko (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The specifics of certain tasks, which are solved by a collimator, as well as the large amounts of light losses in the optic materials which are used in the shortwave and longwave range of the optical specter require the development of mirror and mirror-lens systems. An advantage of these systems is the increased light transmission, small length and the possibility to correct the chromatic abberations. It should only be noted that in the two-component pancratyc systems with reflecting planes with constant optic characteristics there is a danger of illumination of the image plane by side rays – side illuminations. In two-mirror pancratyc system for a collimator it is necessary to exclude illumination of the image plane throughout the whole range of the components movement. In the development process formulas are derived and schemes are presented which help the vizualization when calculating the diaphragm in front of two-mirror pancratyc system and calculation of diaphragm which is located between the components of two-mirror pancratyc system. The results from the calculations of a diaphragm for two-mirror pancratyc system are presented in tables. The results from research of the diaphragms for two-mirror pancratyc sysmem make us conclude that the second method of preventing the image plane from side illuminations is the preferred one. It ensured smaller sized and less change in the diaphragm length.